PENGARUH BEBAN KERJA DAN JOB- INSECURITY TERHADAP STRES KERJA PADA KARYAWAN DI PT. INTIDRAGON SURYATAMA MOJOKERTO - Risti Meinasari; Nurwidji; Fardiansyah, Arief (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Workload and job insecurity are two main factors that support each other and influence stress that occurs in employees. A workload that is too high can make employees feel stressed and overwhelmed. This can cause stress both physically and mentally plus feelings of insecurity at work. The aim of this research is to analyze the influence of workload and job insecurity on work stress among employees at PT. Intidragon Suryatama Mojokerto. The research design used correlational analytic with a cross sectional approach. The total population was 2500 respondents, a sample of 97 respondents was taken using random sampling techniques. The measuring tool used questionnaire, the results are processed through the stages of editing, coding, scoring, tabulating and analyzed by using the Spearman Rho test. The research results showed that there was no influence of workload on job stress (pvalue= 0.50), there was an influence of job insecurity on job stress (pvalue=0.036). The higher the level of job insecurity, the higher the level of work stress, conversely, the higher the workload does not guarantee that the work stress felt by employees will be higher